[The Chinese massacre ; Ecotourism in Palawan ; The Irreverent Leo [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
An investigative report on Chinese community being singled out for kidnapping for ransom. The opening of Palawan to tourists yet preserving its beauty. Interview with Leo, the next superstar comedian.
The Chinese massacre (15 min.) -- Ecotourism in Palawan (14 min.) -- The Irreverent Leo (13 min.)
VHS.
Keywords: Martinez, Leo -- Interviews; Kidnapping -- Philippines; Male actors -- Philippines; Palawan -- Description and travel